Oftalmopati Graves: Patofisiologi, Diagnosis, dan Manajemen - Sihombing, Meri Estivo; Tallo, Nikolaus Lizu (PT Kalbe Farma Tbk., 2024)
Graves ophthalmopathy (OG) is an inflammatory disorder of orbital tissue associated with autoimmune thyroid disease. The complex interaction of endogenous and exogenous or environmental (modifiable) factors are known to trigger the occurrence of OG. The symptoms can have a negative impact on the patient’s quality of life, both physical and psychosocial, and become a burden on public health costs. Early diagnosis, management, and immediate referral to related specialists are very important to prevent the progression of the disease.